2013
DOI: 10.1186/1471-2296-14-20
|View full text |Cite
|
Sign up to set email alerts
|

Barriers, facilitators and attitudes influencing health promotion activities in general practice: an explorative pilot study

Abstract: BackgroundThe number of chronically ill patients increases every year. This is partly due to an unhealthy lifestyle. However, the frequency and quality of (evidence-based) health promotion activities conducted by Dutch general practitioners (GPs) and practice nurses (PNs) are limited. The aim of this pilot study was to explore which lifestyle interventions Dutch GPs and PNs carry out in primary care, which barriers and facilitators can be identified and what main topics are with respect to attitudes towards he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
152
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(171 citation statements)
references
References 20 publications
13
152
1
Order By: Relevance
“…Indicated and disease -oriented prevention use individual interventions as a tool, while universal and selective prevention are mostly community based. We have also described other distinctions that are used to classify HP in Appendix 1 [8]. These distinctions are also used by main stakeholders to describe responsibilities regarding the funding and financing of HP.…”
Section: The Netherlandsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indicated and disease -oriented prevention use individual interventions as a tool, while universal and selective prevention are mostly community based. We have also described other distinctions that are used to classify HP in Appendix 1 [8]. These distinctions are also used by main stakeholders to describe responsibilities regarding the funding and financing of HP.…”
Section: The Netherlandsmentioning
confidence: 99%
“…The national strategy that regulates HP for older adults is based on several policy documents and it is best reflected through integrated prevention based programs such as Nationaal Programma Ouderenzorg [9] and BeterOud (BeterOud.nl). The main goal of this program is to provide healthy independent living of older adults including fall prevention, mental health prevention and social inclusion [8,10]. On the local level, the main role for HP for older adults is given to municipalities and the GGD.…”
Section: The Netherlandsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, it has been shown that GPs are concerned about potentially detrimental effects for the patient-doctor relationship in giving lifestyle advice to patients they know well, 27 and there are many barriers to the effective delivery of health promotion advice and lifestyle counselling. 28,29 Patients report that a more personal relationship with their GP 'created motivation and an obligation to change', however, with the delivery of lifestyle counselling in primary care settings.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…The change of role and modern communication techniques are beyond the traditional patterns of GPs' training and professional work, and there is room for improvement in the pre-and postgraduate medical education in regard to communication training [8]. Besides that, there are multiple barriers to be considered towards the implementation of health promotive counseling in ambulatory primary care, such as low self-efficacy in regard to counseling skills, lack of time, and low reimbursement [9][10][11]. Our study provides further knowledge about the effects of a GP training program in modern communication techniques.…”
Section: Introductionmentioning
confidence: 99%